EDITORIAL - Kadankavil, Thomas (Journal of Dharma, 1988)
On September 5, 1988 the birth centenary of S. Radhakrishnan, a philosopher-statesman from the East, who tirelessly struggled to bring about the meeting of the East and the West in all spheres of life, was celebrated all over India with a variety of programmes. He is foremost among many who believed that the future of religion consists in a free fellowship of faiths whereby mutual contacts of faiths will acquire a new spirit and a new life. Cold metal never mixes; only when thrown into the fire its hardness melts and it thus gives rise to a new alloy. It is an impressive phenomenon of our times that science is forcing us into a global unification of our earthly life. This meeting of differing cultures cannot stay neutral; hostelities have to grow into friendship, mistrust into trust and finally one has to find ways and means to reconcile ones way of thinking and believing with others. The present issue of Journal of Dharma takes up this problem of reconciliation between the conflicting interests in the religio-cultural context of the East and the West. A few articles in this number deal with what S. Radhakrishnan, a philosopher of synthetic or integral vision, has contributed on this issue of the union of the opposites.